THE INFLUENCE OF WORK FIELD PRACTICES, SELF-EFFICACY, AND FAMILY ENVIRONMENT ON THE WORK READINESS OF STUDENTS - Anindya, Feny; Marsofiyati; Adha, Maulana Amirul (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The purpose of this research is to determine the influence of Field Work Practice, Self-Efficacy, and Family Environment on the Job Readiness of students from SMK Negeri 40 Jakarta. The research method used in this study is a survey method with a quantitative approach. The population in this study consists of 196 students from SMK Negeri 40 Jakarta. The sampling technique used is proportionate stratified random sampling with the Slovin formula, with a level of difficulty accuracy of 5%, resulting in a sample size of 132 students. The data analysis technique used in this research is Structural Equation Modeling (SEM) PLS using SmartPLS 4.0 software. The data analysis techniques in this research consist of measurement model analysis, structural model analysis, and testing the hypotheses of direct influence. The results show that variable X1 to Y has an original sample value of 0.254, t-statistics of 3.164 > 1.96, and a p-value of 0.001 < 0.05. The results for X2 to Y have an original sample value of 0.192, statistics of 2.565 > 1.96, and a p-value of 0.005 < 0.05. Then, the results for X3 to Y have an original sample value of 0.370, t-statistics of 3.343 > 1.96, and a p-value of 0.000 < 0.05. The F-Square calculation results for variable X1 to Y are 0.288. The F-Square value for variable X2 to Y is 0.179. The F-Square value for variable X3 to Y is 0.189. The results of this research indicate that there is a positive and significant direct influence simultaneously between Field Work Practice, Self-Efficacy, and Family Environment on Job Readiness.